INTERPRETASI PASAL 51 UNDANG-UNDANG NOMOR 5 TAHUN 1999 DIKAITKAN KONFLIK KEPENTINGAN MERGER BANK SYARIAH BUMN - Muhammad Rizky Ramadhan (2022)
This study was conducted to describe the legal interpretation of Article 51 of Law Number 5 of 1999 on the merger of state-owned Islamic banks which exclusivity of certain business enterprises to conduct monopoly practices in certain business sectors based on the rule of reason approach. This writing is motivated by the act of mergers of 3 SOEs into one state-owned enterprise engaged in the Islamic banking sector which exceeds the threshold for conducting a merger. The results of the study reveal that the restrictive interpretation of Article 51 of Law 5/1999 on the merger of SOE Islamic banks exceeds the limit provided by other laws and regulations, which is stated in Articles 28-29 of Law 5/1999 juncto. PP 57/2010, but is excluded as stated in Article 51 of Law 5/1999. This research was carried out in a normative juridical manner, with a legal approach and a conceptual approach. The conclusion is drawn based on the principle of legal certainty and the theory of legal interpretation, with the result that Article 51 of Law 5/1999 provides exceptions to actions that cause unfair competition and monopoly over certain business entities based on a rule of reason approach.